Login
Remember
Register
Home
All Activity
Q&A
Questions
Hot!
Unanswered
Tags
Categories
Users
Ask a Question
Ask a Question
`4t – 3 – (3t +1) = 5t –
0
votes
asked
Jan 18, 2022
in
8th-maths
by
krutika
(
1.7k
points)
`4t – 3 – (3t +1) = 5t – 4`
marks2
chapter4
#sub
Please
log in
or
register
to answer this question.
0
Answers
Categories
All categories
Maths
(8.6k)
12th-maths
(0)
11th-maths
(0)
10th maths
(0)
9th-maths
(0)
8th-maths
(8.6k)
Science
(14)
Physics
(3.4k)
Related questions
Subtract : `3t^4 – 4t^3 + 2t^2 – 6t + 6` from `– 4t^4 + 8t^3 – 4t^2 – 2t +
Subtract : `3t^4 – 4t^3 + 2t^2 – 6t + 6` from `– 4t^4 + 8t^3 – 4t^2 – 2t +
5t – 3 = 3t –
5t – 3 = 3t –
5t – 3 = 3t –